Pengurangan Emisi pada Kendaraan Menggunakan Kaolin Alam sebagai Adsorben di Kota Lhokseumawe - Putra, Alfian; Wijaya, Nanang R; Fauzan, Reza; Handayani, Utari (Politeknik Negeri Lhokseumawe, 2024)
This study aims to utilize kaolin as a membrane to reduce CO emissions in vehicles. The study was designed with constant variables including 10% PVA, 10% TiO2 catalyst, 8% starch adhesive, and 130 ml of distilled water, resulting in a total mixture weight of 140 grams. The membrane dimensions were 70 mm in length and 50 mm in diameter, with 19 holes of 3 mm each. Independent variables included kaolin carbon ratios (6:1, 5:1, 4:1, 3:2, 1:1) % of total mixture weight, engine rotation (1000, 2000, and 3000) rpm, and sintering temperatures (800°C, 900°C).The CO absorber is a component of the exhaust system designed to reduce carbon monoxide content in exhaust gases from internal combustion engines. CO absorbers typically consist of noble metal catalyst plates (such as platinum, palladium, and rhodium) embedded on ceramic or metal substrates. When exhaust gases pass through the CO absorber, catalytic reactions occur on the catalyst surface, converting carbon monoxide into carbon dioxide (CO2), which is safer for the environment. The study results showed that membranes with a composition of 65.8 g kaolin and 35 g activated carbon absorbed 84.64% of CO exhaust gases, achieving a final CO concentration of 0.80% at 1000 rpm. At 2000 and 3000 rpm, membranes with a composition of 72.8 g kaolin and 28 g activated carbon absorbed 90.45% and 92.31% of CO exhaust gases, with final CO concentrations of 0.57% and 0.54%, respectively. These results comply with the Ministerial Regulation No. 05 of 2006, which sets the CO emission threshold at 1.5% for the year 2007.